Mister Rogers' Neighborhood. Adventures in friendship [videorecording (DVD)] - Rogers, Fred; Aberlin, Betty (Anchor Bay Entertainment, 2005)
"Friends": Mister Rogers visits a restaurant and is invited to talk with the chef. When members of the Neighborhood have trouble cooperating, Lady Aberlin helps them work together. "Love": Mister Rogers hears a lullaby performed on a mandolin. Lady Aberlin sees King Friday and Queen Sara have an argument and learns that even people who love each other can also have angry feelings sometimes.